1991
DOI: 10.1007/bf00169904
|View full text |Cite
|
Sign up to set email alerts
|

Dehalogenation of a mixture of chloroaromatics by immobilized Pseudomonas sp. US1 ex cells

Abstract: Pseudomonas sp. US1 ex e n t r a p p e d in calcium alginate c o u l d d e h a l o g e n a t e a mixture o f i s o m e r i c m o n o c h l o r o b e n z o a t e s a n d 2 , 4 -d i c h l o r o p h e n o x y a e e t i c acid. Rates o f d e h a l o g e n a t i o n by the i m m o b i l i z e d cells were f o u n d to be c o m p a r a b l e to those o f free cells. C o n d i t i o n s for o p t i m u m d e h a l o g e n a t i o n o f c h l o r o a r omatics by i m m o b i l i z e d cells and their reusability were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Similarly, a mixed culture of strains 3mT and P. stutzeri SPC-2, another phenol-degrader with an ortho-pathway also was shown to degrade both these substrates simultaneously (Jayachandran and Kunhi, 2009). However, there seems to be no report on degradation of these two compounds simultaneously by immobilized cells of any organisms, although there have been several reports of degradation of phenol (Agarry et al, 2008;Ahamad and Kunhi, 2011) and a few reports on catabolism of 3-CBA (Sahasrabudhe et al, 1991;Yun et al, 2009) separately by immobilized microbes. In the present study, the complete disappearance of 2 mM each of phenol and 3-CBA occurred within 6 and 7 h, respectively with the release of stoichiometric amounts of Cl¯ whereas with free cells the disappearance of the same amounts of substrates took more than 9 h and the complete mineralization with the release of stoichiometric amount of Cl¯ took about 24 h (Babu et al, 1995a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a mixed culture of strains 3mT and P. stutzeri SPC-2, another phenol-degrader with an ortho-pathway also was shown to degrade both these substrates simultaneously (Jayachandran and Kunhi, 2009). However, there seems to be no report on degradation of these two compounds simultaneously by immobilized cells of any organisms, although there have been several reports of degradation of phenol (Agarry et al, 2008;Ahamad and Kunhi, 2011) and a few reports on catabolism of 3-CBA (Sahasrabudhe et al, 1991;Yun et al, 2009) separately by immobilized microbes. In the present study, the complete disappearance of 2 mM each of phenol and 3-CBA occurred within 6 and 7 h, respectively with the release of stoichiometric amounts of Cl¯ whereas with free cells the disappearance of the same amounts of substrates took more than 9 h and the complete mineralization with the release of stoichiometric amount of Cl¯ took about 24 h (Babu et al, 1995a).…”
Section: Discussionmentioning
confidence: 99%
“…There ISSN (print): 1823-8262, ISSN (online): 2231 are only a few reports on degradation of chlorobenzoates by immobilized systems. Sahasrabudhe et al (1991) have reported dehalogenation of mixtures of monochlorobenzoates and 2, 4-dichlorophenoxyacetic acid by Ca-alginate entrapped cells of Pseudomonas sp. US1 ex, the rates of dehalogenation being comparable to that of free cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These immobilized cells are also favourable for investigation of cell physiology and the dissolution of such gel particles (and thus the liberation of the immobilized cells) is easy and rapid. This technique has gained great scientiWc interest and has been used extensively by researchers in degradation studies of compounds such as phenols [35], pentachlorophenols [36], polychlorinated biphenyl [9], 3-chloroanilines [19], and a mixture of monochlorobenzoates and 2, 4-dichlorophenoxyacetic acid [37].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, calcium alginate-entrapped cells of the constructed strain Pseudomonas sp. strain USlex (410) in a fluidized-bed column reactor were used for the continuous dehalogenation of a mixture of the herbicide 2,4-D and all three isomeric monochlorobenzoates (411).…”
Section: Application Of Microbial Systems In Environmental Protectionmentioning
confidence: 99%